Inner talk - Progressive Awareness Research ([S.l.] : Progreesive Awareness Research Inc. [production company] ; Innertalk Sdn. Bhd., 2002)
This programs are mind training tools which is designed to help individuals change thought, behavior and their neative feelings
vol. 1. Accelered learning and study - vol. 2. Freedom from stress - vol. 3. Respect and good manners - vol. 4. Soaring self-confidence- vol. 5. Stop smoking vol. 6. Learn easily - vol. 7. Health and healing - vol. 8. Stress free - vol. 9. Optimum fitness - vol. 10. Sport hypnosis - vol. 11. Accelerated learning - vol. 12. Power learning and memory - vol. 13. Using both halves of the brain - vol. 14. ADHD - vol. 15. Excelling at sports - vol. 16. Maximum motivation
Keywords: Self-help techniques; Self-talk.; Self-actualization (Psychology).